Memahami Secara Komprehensif Pemikiran dan Pemikiran filsafat Al-Farabi - Muhammad Irfan Maulana; Muhammad Fadhillah Nursyabana; Elza Izzul Aryas; Novianti; Muhammad Parhan (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This article examines Al-Farabi’s philosophical thought, particularly his metaphysical views, theory of intellect, and the relationship between philosophy and religion. Al-Farabi explains the creation of the universe through the concept of emanation and classifies sciences based on ontological and ethical foundations. He emphasizes that philosophy and religion share the same goal of conveying truth, despite using different methods. In politics, he proposes the ideal state led by a philosopher-prophet. His ideas remain relevant today, especially in education and character development.